PENGARUH KEBIJAKAN DIVIDEN, KEBIJAKAN HUTANG DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SEKTOR ANEKA INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2020 - ,Fitri, Mega wati pulungan ,Andewi Rokhmawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to examine the effect of dividend policy, debt policy, and profitability on firm value. This research was conducted on various industrial sector manufacturing companies listed on the Indonesia Stock Exchange by taking data through the official website of the Indonesia Stock Exchange (IDX) www.idx.co.id and www.finance.yahoo.com.  This research was conducted in the period 2016-2020. The population in this study amounted to 51 companies, while the sample in this study amounted to 40 companies using purposive sampling method. Data analysis used multiple linear regression. The results of this study indicate that: dividend policy has a significant positive effect on firm value, debt policy has a significant positive effect on firm value, profitability has a significant positive effect on firm value. Keywords: Dividend Policy, Debt Policy, Profitability and Firm Value